An Approach to Situational Data Integration Based on Data Service Hyperlink - Guiling Wang; Feng Zhang; Yanbo Han (Dianxin kexue)
Enlightened by web page hyperlink，a novel abstraction“data service hyperlink”for linking and integrating data was proposed.With the help of “data service hyperlink”，users can explicitly describe the relationship between data sources.Based on data service hyperlink，the approach to just-in-time data service construction was proposed to enable users integrate data while navigating data services.A data service hyperlink recommendation algorithm was also discussed to help users select proper data service hyperlink to deal with the temporary requirements.A case-study and some experiments how to build a situational data integration application based on data service hyperlink efficiently were presented.